Kinerja Lingkungan, Biaya Lingkungan dan Kinerja Keuangan: (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Sektor Manufaktur periode 2019-2021) - Adinda Maharani Putri Rahayudi; Apriwandi Apriwandi (Politeknik Ganesha Medan, 2023)
The purpose of this study is to ecamine the effect of environmental costs on financial performance mediated by environmental performance listed on the IDX 2019-2021. Financial performance in this study is measured by Return on Assets (ROA). The population in this study are manufacturing companies listed on the IDX during the 2019-2021 period. The sampling technique used purposive sampling, which consisted of 41 companies. The results of this study indicate that environmental costs have no effect on environmental performance, environmental costs have no effect on financial performance, environmental performance have a positive effect on financial performance, and environmental performance is unable to mediate the effect of environmental costs on financial performance.